Experimental and numerical investigation of a freefall wedge vertically entering the water surface. (June 2015) - Wang, Jingbo; Lugni, Claudio; Faltinsen, Odd Magnus
Highlights: Experiments and numerical methods are developed to investigate the water entry of freefall wedges. Experiments showed that a typical water entry of a freefall wedge can be divided into slamming, transition, collapse and post-closure stages. A novel two-fluid BEM is proposed to investigate the influence of the air flow before the closure of the cavity created on the top of the wedge. It is found that for the closure of the 2D cavity, the air flow starts to play an important role just before closure but due to the short duration, the influence of air flow is limited. The results of the numerical model are compared to experiments and good agreements are obtained before the post-closure stage. Abstract: Experiments and numerical methods are developed to investigate the water entry of a freefall wedge with a focus on the evolution of the pressure on the impact sides (the side contacting water) and the top side (the dry side on the top of the wedge), evolution of the global hydrodynamic loads, evolution of the air–water interface, and wedge motion. It is found that a typical water entry of a freefall wedge can be divided into slamming, transition, collapse and post-closure stages. A single-fluid numerical model is presented to simulate the first three stages. The results are compared to experiments and good agreements are obtained. A two-fluid BEM is proposed to investigate the influence of the air flow before the closure of the cavity created on the top of the wedge. It is found that for the closure of the 2D cavity, the air flow starts to play an important role just before closure but due to the short duration, the influence of air flow on the body velocity and configuration of the air–water interface is limited.